KAJIAN ORNAMEN MESJID HUNTO SULTAN AMAY GORONTALO - Risti Puspita Sari Hunowu (Universitas Komputer Indonesia, 2019)
This research is aimed at studying the Hunto Sultan Amay Mosque located in Gorontalo City. Hunto Sultan Amay Mosque is the oldest mosque in the city of Gorontalo The Hunto Sultan Amay Mosque was built as proof of Sultan Amay's love for a daughter and is a representation of Islam in Gorontalo. Researchers will investigate the visual form of the Hunto Sultan Amay Mosque which was originally like an ancient mosque in the archipelago. can be seen from the shape of the roof which initially used an overlapping roof and then converted into a dome as well as mosques in the world, we can be sure the Hunto Sultan Amay Mosque uses a dome roof after the arrival of Dutch Colonial. The researcher used a qualitative method by observing the existing form in detail from the building of the mosque with an aesthetic approach, reviewing objects and selecting the selected ornament giving a classification of the shapes, so that the section became a reference for the author as research material. Based on the analysis of this thesis, the form of the Hunto Sultan Amay mosque as well as the mosques located in the archipelago and the existence of ornaments in the Hunto Sultan Amay Mosque as a decorative structure support the grandeur of a mosque. On the other hand, Hunto Mosque ornaments reveal a teaching. The form of a teaching is manifested in the form of motives and does not depict living beings in a realist or naturalist manner. the decorative forms of the Hunto Sultan Sultan Mosque in general tend to lead to a form of flora, geometric ornaments, and ornament of calligraphy dominated by the distinctive colors of Islam, namely gold, white, red, yellow and green.